Randomized, direct comparison study of Saccharomyces boulardii CNCM I-745 versus multi-strained Bacillus clausii probiotics for the treatment of pediatric acute gastroenteritis - Altcheh, Jaime Marcelo (2022)
Background: The choice of an appropriate probiotic for pediatric acute gastroenteritis (PAGE) can be confusing. Our aim was to compare the efficacy and safety of 2 probiotics (Saccharomyces boulardii CNCM I-745 vs a 4-strain mixture of Bacillus clausii O/C, SIN, N/R, T) for the treatment of PAGE. Methods: A 2-arm parallel, randomized trial recruited children (6 months to 5 years old) with mild-moderate acute diarrhea, from 8 centers in Argentina. A total of 317 children were enrolled and blindly randomized to 5 days of either S boulardii CNCM I-745 (n = 159) or a 4-strain mixture of B clausii (n = 158), then followed for 7 days post-probiotic treatment. A stool sample was collected at inclusion for pathogen identification. The primary outcome was duration of diarrhea defined as the time from enrollment to the last loose stool followed by the first 24-hour period with stool consistency improvement. Secondary outcomes included frequency of loose stools/day, severity of diarrhea, number reporting no diarrhea at Day 6, time-to-first formed stool, recurrence of diarrhea by study end (Day 12) and safety outcomes. Results: Three hundred twelve (98%) children completed the study. S boulardii CNCM I-745 showed a significant reduction (P =.04) in the mean duration of diarrhea (64.6 hours, 95% confidence interval [CI] 56.5-72.8) compared to those given B clausii (78.0 hours, 95% CI 69.9-86.1). Both probiotics showed improvement in secondary outcomes and were well-tolerated. Conclusion: In this study, S boulardii CNCM I-745 demonstrated better efficacy than B clausii mix for reducing the duration of pediatric acute diarrhea.